POLITENESS STRATEGIES AS STYLISTIC DEVICES: PRAGMATIC FUNCTIONS OF HONORIFICS AND MODALITY ENGLISH VS. UZBEK ACADEMIC DISCOURSE - Abdubokieva, Dilshoda (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
Academic writing constructs scholarly authority through culturally specific politeness strategies. This study compares how English and Uzbek research articles employ these strategies to balance credibility with interpersonal sensitivity. Analysis of 200 articles (100 per language) reveals a key contrast: English academic discourse relies on epistemic modality-modal verbs (may, might, could) and hedging-to express tentativeness and mitigate face threats. Uzbek academic writing, by contrast, encodes respect through formal address pronouns, kinship-based terms, and morphological honorifics that reflect hierarchical, collectivist norms. These differences highlight how politeness functions as a stylistic device shaped by cultural pragmatics. The topic raised in the article covers not only the fields of linguistics and pragma-stylistics, but also has relevance in the context of academic communication and intercultural education. Politeness strategies, in particular, modal and honorific means used in academic writing, form interactive and normative norms between students and members of the academic community. In this regard, the results of the article can be useful not only for comparison, but also in pedagogical and translation studies practice. For example, the incorrect use of epistemic modality and hedging by Uzbek students writing academic articles in a foreign language or the use of perfect hedging in English can lead to misunderstandings in assessing their academic status. At the same time, the article identifies, from a cultural perspective, the competencies necessary for effective communication in the global academic community by combining the epistemic and social functions of language tools. This approach also emphasizes the need to study international academic writing and take into account intercultural differences in academic translation. In addition, the article provides an analysis of the role and effectiveness of politeness strategies in the interactive part of academic writing (author-reader relationships, comments, and the peer-review process). This contributes to a deeper understanding of not only the grammatical and lexical aspects of academic writing, but also its pragmatic and cultural aspects.